Association between skilled maternal healthcare and postpartum contraceptive use in Ethiopia - Gizachew Assefa Tessema; Tensae Tadesse Mekonnen; Zelalem Birhanu Mengesha; Katherine Tumlinson (BMC, 2018)
Abstract Background The postpartum period provides an important opportunity to address unmet need for contraception and reduce short birth intervals. This study aims to assess the association between skilled maternal healthcare and postpartum contraceptive use in Ethiopia. Methods Data for this analysis come from the 2011 to 2016 Ethiopian Demographic and Health Surveys (EDHS) and include nearly 5000 married women of reproductive age with a recent birth. Multivariate logistic regression was conducted to investigate the relationship between skilled maternal healthcare and postpartum contraceptive use. Results Between rounds of the 2011 and 2016 EDHS, the postpartum contraceptive prevalence increased from 15 to 23% and delivery in public facilities, use of skilled birth assistance, and skilled antenatal care also grew. In both survey rounds, educated women had approximately twice the odds of postpartum contraceptive use, compared with non-educated women, while an initially significant relationship between wealth and postpartum contraceptive use diminished in significance by 2016. Women with a desire to limit future pregnancy had five to six times the odds of postpartum contraceptive use in both survey rounds, and women in 2016 - unlike those in 2011 - with a desire to delay pregnancy were significantly more likely to use contraception (adjusted odds ratio (AOR) = 4.38, 95% CI: 1.46-13.18) compared to women who wanted another child soon. In 2011, no statistically significant associations were found between any maternal healthcare and postpartum contraceptive use. In contrast, in 2016, postpartum contraceptive use was significantly associated with an institutional delivery (AOR = 1.71, 95% confidence interval (CI): 1.12-2.62) and skilled antenatal care (AOR = 2.41, 95% CI: 1.41-4.10). No significant relationship was observed in either survey round between postpartum contraceptive use and skilled delivery or postnatal care. Conclusions A comparison of postpartum women in the 2011 and 2016 EDHS reveals increased use of both contraception and skilled maternal healthcare services and improved likelihood of contraceptive use among women with an institutional delivery or antenatal care, perhaps as a result of increased attention to postpartum family planning integration. Additionally, results suggest postpartum women are now using contraception to space future pregnancies, with the potential to help women achieve more optimal birth intervals.